PERSEPSI MAHASISWA AKUNTANSI FAKULTAS EKONOMI UNIVERSITAS SLAMET RIYADI SURAKARTA TERHADAP MINAT BERKARIR SEBAGAI AKUNTAN PUBLIK - Djoko Kristianto, Dewi Handayani, Rispantyo & (Universitas Slamet Riyadi, 2017)
This study aims to determine how perceptions of accounting students ofUniversity Slamet Riyadi Surakarta (UNISRI)) against the election of a career as apublic accountant.The results of this study indicate that simultaneous factor financialrewards, professional training, social values, work environment, labor marketconsiderations, personality, and professional recognition has a significant influenceon the selection of a career as a public accountant by accounting students at theUniversity Slamet Riyadi Surakarta. Partially factors financial reward, workenvironment, labor market considerations, and personality has a significantinfluence on the selection of a career as a public accountant by accounting studentsat the University Slamet Riyadi Surakarta, while the professional training factor,social values, and a professional recognition has no influence significantly to theselection of a career as a public accountant by accounting students at the UniversitySlamet Riyadi Surakrta.Keywords: interest in becoming a public accountant, finansial rewards, professionaltraining, social values, work enviroment, labor market, professionalrecognition.